Pengaruh Variasi Kecepatan Putaran Benda Kerja Dan Kedalaman Pemakanan Terhadap Kekarasan Permukaan Proses Gerinda Silinderis Baja AISI 4140 Menggunakan Media Pendingin (Coolant Campuran Minyak Sawit Dan Calcium Hypochlorite) - Arief, Dodi Sofyan (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Selection of the appropriate grinding parameters are needed and grinding parameters that affect the quality of surface roughness such as rotation speed grinding machines, the speed of rotation of the workpiece using the coolant medium is coolant mixture is in the form of palm oil additives RBDO with calcium hypochlorite. Coolant mixture is obtained based on the results of research that has been done by Buma in 2014. This study used three variations of round rotation workpieces are low speed (83 rpm), medium speed (194 rpm) and high speed (304 rpm). Likewise with varying depth of cut is 0.005 mm, 0.010 mm, 0.015 mm. This test is a variation on the round grinding machine and workpiece feeds depth very big influence on the surface roughness. In this case can be concluded that the greater the level of rotational speed of the workpiece and the depth of feeds, then the smaller the surface roughness value is in the variation of the rotational speed of the workpiece at a speed of 304 rpm with a depth of 0.015 mm Ingestion is worth 0.84 Î¼m. The lower level of the rotational speed of the workpiece and the depth of feeds, the greater the surface roughness value is in the variation of the rotational speed of the workpiece at a speed of 83 rpm with a depth of 0,005 mm Ingestion is worth 2.43 Î¼m.Keywords: Surface roughness, Grinding machine, Depht of feeds and Depht of cut